Fertilitu zachovávající léčba borderline tumoru ovaria - kazuistika - Železná Teyschlová, M; Rob, L; Robová, H; Pluta, M; Machač, J (Ceska gynekologie, 2015)
The borderline tumors are known as low malignant potential tumors. Usually younger women suffer for them, than by the invasive ovarian carcinoma. They often which to be pregnant. The fertility-sparing surgery is posile but contain higher risk of the new disease on contralateral ovary.
Keywords: Fertility; Ovariectomy; Decision Trees; Ovarian Neoplasms; ovaria borderline tumor; Pregnancy; těhotenství; rozhodovací stromy; nádory vaječníků; prognosis.; fertility-sparing surgery; fertilita; lidé; ženské pohlaví; ovarektomie; adenokarcinom; Humans; Adenocarcinoma; Female